Evaluating the IEEE 802.15.4a UWB physical layer for WSN applications - Saadon, Eddy Irwan Shah (2013)
Wireless communications are becoming an integral part of our daily lives such as wireless local area networks (WLANs) and wireless sensor networks (WSNs). Since more and more devices are going wireless today, it is essential that future wireless technologies can coexist with each other. Ultra wideband (UWB) is a promising solution to this problem due to can coexist with other wireless devices, make it a good candidate for short to medium range wireless system such as WSNs. This research presents the analysis of the IEEE 802.15.4a UWB physical layer (PHY), a novel short range wireless communication technology, for wireless sensor network applications. We analysed and compared the performance of the UWB PHY using the MIXIM framework for a discrete event based simulator called OMNeT++. Among the objectives of our study is to compare the performances by evaluate the bit error rate (BER), throughput and impact of Reed Solomon (RS) coding. In this context, we simulated various types of channels – free space path loss, Ghassemzadeh statistical indoor channels and IEEE 802.15.4a channel models with a variety of configurations such as data rate, bandwidth and forward error correction. An analysis on BER over distances and throughput will be discussed to evaluate the channels performance. The simulation results can be explored for planning and deploying IEEE 802.15.4a based sensor networks with specific performance demands. Besides, specific protocol limitations in real time environment can be identified and solutions can be suggested.